If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6x+4(x-6)=-16
We move all terms to the left:
-6x+4(x-6)-(-16)=0
We add all the numbers together, and all the variables
-6x+4(x-6)+16=0
We multiply parentheses
-6x+4x-24+16=0
We add all the numbers together, and all the variables
-2x-8=0
We move all terms containing x to the left, all other terms to the right
-2x=8
x=8/-2
x=-4
| 5a+5a+a-9a=10 | | y/5-6=9Y= | | X+20=2x-65 | | f(1/2)=(1/2)^2-3(1/2)+2 | | 78/3*10-x=249 | | (x÷2)+3=15 | | 3x3+2x+5=0 | | 15m-4m-9m-2m+3m=18 | | 5t+8+11t=7 | | 2.5t=1.625 | | 45m-900=9m | | 2b-b=14 | | 256^x+2=4^3x+9 | | 4(-2x-7)-5=-89 | | 5y-2y=18 | | m^2=56+m | | 0.624869351909=4x+2/5x | | 2+(x+4)=-3 | | 18t-13t=15 | | 3x(x^2-7x-10)=0 | | 54/x+254=263 | | 4+8(2+8x)=148 | | 5/x+7=3/x=2 | | (-4/3y+1)+2=y | | 6m−5m=19 | | 2x/5-4/5=x+4 | | 12b-3b=18 | | 3/5w=142/5 | | 3x^2+5=13 | | 3s-4s=63 | | 9y-8=-9 | | x/8+8=16 |